2018
DOI: 10.1177/0269881118756061
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide prevents metabolic side-effects and improves recognition and working memory during antipsychotic treatment in rats

Abstract: Liraglutide co-treatment improved aspects of cognition, prevented obesity side-effects of olanzapine, and the hyperglycaemia caused by clozapine, when administered from the start of APD treatment. The results demonstrate a potential treatment for individuals at a high risk of experiencing adverse effects of APDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 97 publications
4
21
0
Order By: Relevance
“…The present study is a continuation of our previous publication (Babic et al, 2018). Briefly, female Sprague Dawley rats ( n = 72, weighing 200–225 g; Animal Resources Centre, Perth, Australia) were individually housed at 22°C on corn cob bedding with plastic tunnels and nesting material for environmental enrichment.…”
Section: Methodssupporting
confidence: 59%
See 2 more Smart Citations
“…The present study is a continuation of our previous publication (Babic et al, 2018). Briefly, female Sprague Dawley rats ( n = 72, weighing 200–225 g; Animal Resources Centre, Perth, Australia) were individually housed at 22°C on corn cob bedding with plastic tunnels and nesting material for environmental enrichment.…”
Section: Methodssupporting
confidence: 59%
“…; Zyprexa; Eli Lilly, Indianapolis, IN) via oral cookie dough pellet, clozapine (12 mg/kg t.i.d., Clozaril; Norvatis, Basel, Switzerland) via oral cookie dough pellet, olanzapine + liraglutide co-treatment, clozapine + liraglutide co-treatment or vehicle (oral cookie dough pellet without drug + SC sterile water; n = 12/group) for six weeks. Olanzapine and clozapine tablets were de-coated and pulverised, and the assigned dosage was added to a cookie dough mixture, as previously detailed (Babic et al, 2018; Weston-Green et al, 2011). A cookie dough pellet (0.3 g) was offered on a metal spoon, and rats were monitored to ensure consumption of each pellet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of preclinical paradigms offers the additional benefit of helping to disentangle the multifactorial causes of metabolic dysregulation in psychiatric illness, where variables such as diet, exercise, and drug use can all contribute to cardiometabolic dysregulation (25)(26)(27). Fortunately, the past 10-15 years has seen significant advances in animal models of the metabolic side-effects of antipsychotic drugs (28), which have demonstrated that many of these compounds cause acute glucose dysregulation and insulin resistance independent of weight gain (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, liraglutide exerts positive effects on weight loss, blood pressure, hyperlipidemia, and glycemic control in the clinic. Thus, many studies have investigated its effects on the cardiovascular, endocrine, and nervous systems (Ishii et al, 2017;Babic et al, 2018;Bahtiyar et al, 2018). In animal models and clinical patients, there were no adverse events or reproductive toxicity found posttreatment with liraglutide.…”
Section: Discussionmentioning
confidence: 99%